Analisis Perubahan Tutupan Lahan di Sub Das Langge Kecamatan Tapa Kabupaten Bone Bolango - Denis Pangulili; Asda Rauf; Yanti Saleh (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
This research analyzes land cover changes in the Langge Sub-watershed, Tapa District, Bone Bolango Regency, over five years from 2019 to 2023. Population growth and increasing land needs are driving significant land use changes. The method used in this study is a quantitative approach with spatial analysis using Sentinel-2 satellite imagery. The analysis results show significant changes in land cover, with water body areas decreasing from 28.50 ha to 21.69 ha, settlements dropping from 55.45 ha to 52.02 ha, and secondary forests experiencing a drastic decline from 462.83 ha to 319.13 ha. Meanwhile, dryland areas increased from 172.24 ha to 227.17 ha, and shrubland experienced a significant increase from 121.07 ha to 247.91 ha. The decline in secondary forest cover is a significant concern because it negatively impacts environmental quality and potentially increases the risk of disasters such as floods and erosion. This research underscores the importance of sustainable management for maintaining ecosystem function and minimizing the negative impacts of land cover change.